PROGRAMMES OF THE EUROPEAN UNION FOR REFORMING OF HIGHER EDUCATION - Shytikova, Svitlana P. (Educological discourse, 2016)
The article is devoted do overview of the key priorities of the European Union funded educational programmes which help to implement reforms in higher education sphere under new Law of Ukraine “On higher education”. The author analyses the outcomes of some educational projects which contributed to the development of capacity to implement new Law of Ukraine “On higher education”. Key and additional resources to ensure effective implementation of international educational and research programmes Erasmus+ and Horizon 2020 are described. The key priorities for higher education reform implementing international cooperation projects have been identified.